Women’s Empowerment in Madura Villages - Rahmawati, Aminah Dewi; Mulyaningsih, Hetti; Hamida, Aliya (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The position of village head (klebun) in Madura is predominantly held by men, suggesting patriarchal power and political dynasties. This study explores how women klebuns responded to the situation by empowering themselves and other women. The analysis uses qualitative descriptive methods and Foucault’s theory of power and legitimacy. Data was collected from observations of 11 women klebuns and in-depth interviews with four of them. The findings reveal that female klebuns face a choice between being extensions of their male relatives or being leaders themselves. To challenge the patriarchal constructs, they strategically use political influence, establish relationships with officials, and seek support from legal aid institutions. These efforts were made to address the issue of village security centering around the Madurese people in order to regain public trust. The study unveils the complexity of women’s empowerment in Madura’s male-dominated political landscape. This encouraged female klebuns to strive and transform the social and political dynamics, advocating for gender equality and challenging existing power structures. This research offers insights into promoting women’s political empowerment at the village level, and fostering gender equity in local governance, inspiring change in Madura and beyond.